Da tradição e guerra justa: o arquétipo da guerra de Diogo do Couto - Fonseca, Sofia Theodoro Prevatto da (2020)
This dissertation has as objective make a study about the Orient portuguese. We will seek deal with the experience of portuguese colonization in Asia in the early years of XVII century - years of empire decay in Goa’s territory – and think about motivations, the contacts and, at the same time, the make politician, existintg in these possession from the chronicler's writings Diogo do Couto. Analising the narrative Diálogo do Soldado Prático, we will search to perceive the fair war enterprise featuring and adjusting through the mechanisms of power and paying attention to the forces and sociabilities existing in the overseas experience. Therefore, we wish to observe the concept of an ideal model about a dynamic process of the crisis.